Impacts of Covid-19 on family income and its influence on the food consumption pattern of children enrolled in basic education in the city of Pederneiras-SP (Research, Society and Development, 2022)
The Covid-19 pandemic has promoted significant changes in people's daily lives, including changes in working conditions and income generation, reflecting on behavior, eating habits and health, affecting children and adolescents much more. Thus, the objective of this work was to investigate the impacts of the pandemic on the income of families with children enrolled in basic education in the city of Pederneiras-SP and its possible implications for the eating behavior of these children. For this, an online quantitative and qualitative research was sent to the families of children enrolled in public schools for kindergarten (EMEI) and elementary school (EMEF) in the city of Pederneiras-SP, and the collected data were statistically analyzed. Among the 1146 participating families, 43.6% had a reduction in income during the pandemic, and the most affected group was the one with the lowest income and the lowest level of education of parents. In those families that received foodstuffs from assistance programs as well as those that increased their income during the pandemic, fruit consumption by children was higher. However, the consumption of ultra-processed foods was also higher among children from families that had increased income in the period and among those whose parents' education level was lower. By promoting changes in dietary patterns, income indirectly influenced children's health status. Thus, considering the importance of eating habits in health and the relationship between food consumption pattern and income, caring for families in the post-pandemic period becomes essential.